(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. This article analyses theoretical foundations of the problem of communicative competence as an integrative formation of a future teacher’s personality. The variability of the definition of “communicative competence” was presented. The different scientists’ approaches to defining the essence and content of the denoted phenomenon were considered. The basic structural and functional components of communicative competence (gnostic, motivational-value, operational-activity, reflexive, personal, emotional-volitional) and their substantive characteristics were specified and defined. According to the results of theoretical analysis, communicative competence is defined as a system of internal reserves of a personality necessary for communicative interpersonal interaction.